Emaciation and immobility due to enormously growing degenerating subserosal fibroid up to mid-thorax during pregnancy and following childbirth-an unusual presentation managed by multidisciplinary approach - Bhadra, Avishek; Mukhopadhyay, Arunima; Dey, Ramprasad; Biswas, Rumela (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Uterine fibroids (leiomyomas) are common neoplasms in women of childbearing age, with prevalence of approximately 10.7% in pregnancy. Subserosal fibroids are typically less symptomatic but can lead to significant complications during pregnancy, such as degeneration and hemorrhage. Large, rapidly growing fibroids, particularly those causing compression and degeneration, present challenges in clinical management, requiring careful consideration of delivery routes, timing, and the preservation of fertility. This case report addresses the complex management of a patient with enormously growing degenerating subserosal fibroids during pregnancy and postpartum. A 32-year-old nulliparous woman presented at 8 weeks gestation with large subserosal fibroids. Despite adequate fetal growth, the fibroids grew substantially during pregnancy, resulting in cachexia, immobility, and dyspnoea by the third trimester. The patient required multiple blood transfusions and frequent monitoring. At 32 weeks, after delivery via category 3 cesarean section, complications arose including postpartum hemorrhage, which was managed with uterotonics. Postpartum, the patient experienced a significant increase in fibroid size, causing further complications such as respiratory distress and abdominal distension. This required a laparotomy followed by myomectomy. The patient underwent successful laparotomy for the removal of the degenerated fibroid cyst, with along with drainage of 38 litres of cystic fluid. Postoperative care involved intensive monitoring, including respiratory management and fluid replacement. Histopathological analysis confirmed the presence of a benign degenerated leiomyoma. The patient’s postoperative recovery was gradual, with significant improvement in her symptoms. This case highlights the rare and challenging scenario of rapidly growing subserosal fibroids in pregnancy and postpartum. The multidisciplinary approach was crucial for managing both phases of the patient’s care during pregnancy to ensure fetal well-being and manage complications, and postpartum to address the growing fibroids. Though uterine subserosal fibroids generally do not impact pregnancy significantly, in rare cases, such as this, they can lead to severe complications requiring surgical intervention.